2021
DOI: 10.1007/s13353-021-00661-0
|View full text |Cite
|
Sign up to set email alerts
|

Different response of perennial ryegrass—Epichloë endophyte symbiota to the elevated concentration of heavy metals in soil

Abstract: The phenomenon of plant mutualistic symbiosis with microbes may have a positive effect on the improvement of plant tolerance to environmental stresses as well as on the ability of plants to accumulate heavy metal (HM) ions from soil. The influence of Epichloë fungal endophyte (Ascomycota, Clavicipitaceae) on perennial ryegrass (Lolium perenne L.) plants grown in the presence of elevated concentrations of HM ions (Cd2+, Pb2+, and Cu2+) in soil was studied. The presence of Epichloë in the host grass tissues resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Significant differences between different cultivars of Lolium perenne seedlings to drought and salinity stress have been previously demonstrated 55 , 56 . Significant influence of differ heavy metals were also shown in fully developed ecotypes of this species 26 . These authors also found, that reaction of photosynthesis of this species on Cd, Pb and Zn contamination can varied among cultivars of this species.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Significant differences between different cultivars of Lolium perenne seedlings to drought and salinity stress have been previously demonstrated 55 , 56 . Significant influence of differ heavy metals were also shown in fully developed ecotypes of this species 26 . These authors also found, that reaction of photosynthesis of this species on Cd, Pb and Zn contamination can varied among cultivars of this species.…”
Section: Discussionmentioning
confidence: 61%
“…It is widely used as a forage crop and as an alternative and renewable bioenergy source. The turf cultivars of perennial ryegrass are widely used for the establishment of lawns in urban areas 25 , 26 . Urban green spaces have numerous functions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [60] found that drunken horse grass infected with E. gansuensis had more biomass and tillers and was taller in height than uninfected grass under cadmium stress. Similarly, studies have found that E+ perennial ryegrass shoot biomass was better in E+ under cadmium stress and had increased amounts of H 2 O and chlorophylls a and b [61,62]. A recent study found that E+ perennial ryegrass accumulated copper and cadmium better than its E-counterparts [62].…”
Section: Heavy Metalsmentioning
confidence: 88%
“…Similarly, studies have found that E+ perennial ryegrass shoot biomass was better in E+ under cadmium stress and had increased amounts of H 2 O and chlorophylls a and b [61,62]. A recent study found that E+ perennial ryegrass accumulated copper and cadmium better than its E-counterparts [62]. When presented with Zn stress, E+ perennial ryegrass showed less Zn accumulation in the leaves and had a higher tiller number and overall biomass.…”
Section: Heavy Metalsmentioning
confidence: 88%
“…A mutualistic symbiosis between plants and microorganisms can increase plant tolerance to environmental stressors [158]. The presence of Epichloë fungal endophytes in host plant tissues increased chlorophyll content, photosystem II efficiency and the accumulation of heavy metal ions in aerial plant parts, and it was influenced by the genotype of the host plant.…”
Section: Fungimentioning
confidence: 99%